Midterm risk of cancer with metal-on-metal hip replacements not increased in a Finnish population - Elina Ekman; Inari Laaksonen; Antti Eskelinen; Pekka Pulkkinen; Eero Pukkala; Keijo Mäkelä (Taylor and Francis Ltd, 2022)
Background and purpose — Metal-on-metal (MoM) total hip arthroplasty (THA) and hip resurfacing arthroplasty (HRA) have been widely used during the early 21st century. We assessed the midterm risk of cancer of patients treated with modern MoM hip implants compared with patients with non-MoM hip implants and the general Finnish population with special interest in soft tissue sarcomas and basalioma due to the findings of our previous report.
Patients and methods — All large-diameter head MoM THAs and hip resurfacings performed in Finland between 2001 and 2010 were extracted from the Finnish Arthroplasty Register (10,728 patients). Patients who underwent conventional THA formed the non-MoM reference cohort (18,235 patients). Data on cancer cases up to 2014 were extracted from the Finnish Cancer Registry. The relative risk of cancer in the general population was expressed as the ratio of observed to expected number of cases, i.e., standardized incidence ratio (SIR). Poisson regression analysis was used to compare the cancer risk between the cohorts. The mean follow-up was 7.4 years (1–14) in the MoM cohort and 8.4 years (1–14) in the non-MoM cohort.
Results — The overall risk of cancer in the MoM cohort was comparable to the general Finnish population (SIR 0.9, 95% CI 0.9–1.0). Risk of basalioma in the MoM cohort was higher than in the general Finnish population (SIR 1.2, CI 1.1–1.4) and higher than in the non-MoM cohort in the stratified regression analysis (RR 1.2, CI 1.0–1.4, p = 0.02). The SIR of soft-tissue sarcoma in the MoM cohort was 1.4 (CI 0.6–2.8); the incidence was same as in the non-MoM cohort.
Interpretation — Metal-on-metal hip implants are not associated with an increased overall risk of cancer during midterm follow-up.